Coping Mechanisms in Schizophrenia Patients: Concept Analysis - Asriyani Asriyani; Darti Darti; Muliani Muliani; Ratna Sari Putri; Sudarwati Safwan; Satriya Pranata; Siti Aisah; Aric Vranada (GLOBAL HEALTH SCIENCE GROUP, 2024)
Coping mechanisms greatly help schizophrenia patients deal with psychotic symptoms such as hallucinations, delusions, and disorganized thoughts, as well as manage the emotional and social effects of their illness. The purpose of this concept analysis is to gain a more detailed and in-depth understanding of the use of coping mechanisms as part of schizophrenia therapy. This concept analysis uses the Walker and Avant approach with relevant literature findings related to the concept were obtained through concept databases such as Google Scholar, PubMed, Scopus, etc. Keywords used in the literature search include